Facile fabrication of nanoporous nickel with rational pore structure decorated with ultrathin Ni(OH)2 nanosheets as advanced supercapacitor electrodes. (15th March 2020) - Ge, Wei; Encinas, Armando; Ruiz, Maria Fernanda; Araujo, Elsie; Song, Shaoxian
Abstract : Nanoporous Ni with rational pore structure decorated with Ni(OH)2 nanosheets (Ni(OH)2 @NPN) was fabricated by a cost-effective process of template-directed electrodeposition combined with surface conversion. Nitrocellulose (NC) template controls the pore structure of NPN with interconnected pore channels and diameters of a few hundred nanometers, which provides short pathways for rapid electrolyte diffusion, and offers enough space for the growth of Ni(OH)2 nanosheets. The direct conversion of Ni(OH)2 nanosheets from the surface metallic Ni of NPN ensures a low contact resistance at the interface and high utilization of Ni(OH)2 . Benefiting from the structural features, Ni(OH)2 @NPN shows significantly improved electrochemical performance. Graphical abstract: Image, graphical abstract